Perilaku Orang Tua Dalam Novel The Best of Me Karya Nicholas Sparks - Lucky Lusiana; Fenty Sukmawaty; Saprudin (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2021)
The Best of Me by Nicholas Sparks tell about the love story of Dawson Cole and Amanda Collier as teenager. Their love story didn’t smoothly because Amanda Collier’s parents already knew Dawson family background and her parents didn’t give permission to them. Aside from that this book tell about parental behavior and how to educating children. Some forms of affection shown by Amanda's and Dawson’s parents are converted in some of their actions towards Amanda and Dawson. In general cases that often occured expecially in the wider community or society, parental education certainly greatly affects to the psychological condition of the child itself. Some examples of educational actions taken by Amanda's and Dawson’s parents are reflected in some of their characteristics which are then analyzed in this analysis. Communication also plays a very big role in the children's behavior alternation. Good communication will two certainly produce a good relationship between the two sides, whether it could be in the child's side or the parents itself. The purpose of the research is to analyze this novel by Nicholas Sparks based on parental behavior. This research is descriptive qualitative research. The object of this research is Nicholas Sparks’ novel, The Best of Me, published in 2012. The data collecting method used is library technique where the documents used in this study are books, transcripts, magazines and notes that are not numbers.